2021
DOI: 10.3390/cells10123503
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent THC Treatment Does Not Potentiate the Behavioral Effects in Adulthood of Maternal Immune Activation

Abstract: Both in utero exposure to maternal immune activation and cannabis use during adolescence have been associated with increased risk for the development of schizophrenia; however, whether these exposures exert synergistic effects on brain function is not known. In the present study, mild maternal immune activation (MIA) was elicited in mice with prenatal exposure to polyinosinic-polycytidylic acid (poly(I:C)), and ∆9-tetrahydrocannabinol (THC) was provided throughout adolescence in cereal (3 mg/kg/day for 5 days)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 48 publications
(57 reference statements)
1
3
0
Order By: Relevance
“…Our results showed PPI reduction in both male and female MIA rats (Figure 2F), in accordance with previous studies (Wischhof et al, 2015); however, in agreement with previous literature, we found no detrimental effects of THC exposure on PPI. Importantly, we found no interaction between MIA and cannabinoid exposure during adolescence, suggesting that there are no summative or synergistic actions between both hits in this model, as reported with other two-hit models (Garcia-Mompo et al, 2020; Guma et al, 2023; Rodríguez et al, 2017; Stollenwerk and Hillard, 2021a).…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Our results showed PPI reduction in both male and female MIA rats (Figure 2F), in accordance with previous studies (Wischhof et al, 2015); however, in agreement with previous literature, we found no detrimental effects of THC exposure on PPI. Importantly, we found no interaction between MIA and cannabinoid exposure during adolescence, suggesting that there are no summative or synergistic actions between both hits in this model, as reported with other two-hit models (Garcia-Mompo et al, 2020; Guma et al, 2023; Rodríguez et al, 2017; Stollenwerk and Hillard, 2021a).…”
Section: Discussionsupporting
confidence: 77%
“…In this work, we have shown that MIA and THC exposure during adolescence do not interact to precipitate schizophrenia-related symptoms in rats, at least not in the behavioural dimensions that we have examined. This adds to the growing number of studies that have experimentally tested the two-hit hypothesis and have found no evidence for synergy between the two hits (Guma et al, 2023; Lecca et al, 2019b; Stollenwerk and Hillard, 2021b). Clearly, we are still at an early stage of research using these two-hit models before we can unmistakably dismiss a precipitating role of cannabis consumption during adolescence in the onset of schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prenatal exposure to viral pathogens, such as influenza, is related to an increased risk of developing schizophrenia in adulthood [ 225 ], and most research has shown increased schizophrenia cases after influenza pandemics [ 226 , 227 ]. The MIA model requires the administration of polyinosinic:polycytidylic acid (poly(I:C)) during the gestational stage to activate the innate immune system dependent on toll-like receptor 3 (TLR-3) signaling [ 225 ]. Some researchers also use LPS to induce an immune response, and this method also qualifies as MIA [ 228 ].…”
Section: Neurodevelopmental Modelsmentioning
confidence: 99%